Efektifitas Tablet Effervescent Ekstrak Kulit Manggis (Garcinia mangostana L) sebagai Pembersih Gigi Tiruan Resin Akrilik terhadap Candida albicans - Jovanna Andhara Arieputri; Dewi Kristiana; R. Rahardyan Parnaadji (Fakultas Kedokteran Gigi Universitas Jember, 2019)
Denture stomatitis is inflammation of the oral mucosa in contact with the denture base caused by the fungus Candida albicans. Denture stomatitis can be prevented by cleaning the dentures either mechanically or chemically. Mangosteen peel extract has been shown to inhibit the growth of C. albicans, but its effectiveness as a denture cleaning agent needs to be improved. One way to increase effectiveness is by combining chemical cleansing and mechanical cleansing through effervescent tablets. The aim of the study was to determine the effectiveness of mangosteen peel extract effervescent tablets as an acrylic denture cleaner against C. albicans. Previously, the effervescent tablets of mangosteen peel extract were made with concentrations of 30% and 60%. Heat cured acrylic resin samples were incubated into a test tube containing C. albicans suspension for 24 hours at 37oC. Furthermore, the samples were immersed in effervescent tablets of mangosteen peel extract for 15 and 30 minutes. The number of C. albicans cells was counted using a spectrophotometer. The results showed that there was a significant reduction in the number of C. albicans cells attached to the plate surface after immersion in 30% and 60% effervescent tablets of mangosteen peel extract (p <0.05). Mangosteen peel extract effervescent tablets 60% more decreased the number of C. albicans cells. The duration of immersion did not show significantly different results (p> 0.05). Effervescent tablets of 60% concentration of mangosteen peel extract soaked for 15 minutes were the most effective as an acrylic resin denture cleaner against C. albicans.